Advancing the Science and Practice of Social and Emotional Learning: Looking Back and Moving Forward. (March 2016) - Osher, David; Kidron, Yael; Brackett, Marc; Dymnicki, Allison; Jones, Stephanie; Weissberg, Roger P.
This chapter summarizes the results of nearly 100 years of research on school-based social and emotional learning (SEL). The SEL field has grown out of research in many fields and subfields with which educators, researchers, and policymakers are familiar, including the promotion of social competence, bullying prevention, prevention of drug use and abuse, civic and character education, emotional intelligence, conflict resolution, social skills training, and 21st-century skills. The chapter begins with a historical summary of theoretical movements and research trends that have led to today's inclusion of SEL as part of many schools' curricula, policies, and practices. Contemporary approaches that represent current policy and societal concerns are discussed in comparative terms. Based on the converging research evidence, this chapter identifies design elements and implementation quality characteristics of effective approaches to SEL. Recommendations for future practice, policy, and research are provided.